A digital euro’s relationship with data protection, anti-money laundering and combating the financing of terrorism - Mesquita, Diogo Machado Teixeira da Mota Dá (2022)
The study focuses on the possibility of a central bank digital currency (CBDC) for the euro area and its relationship with data protection and anti-money laundering / combating the finance of terrorism (AML/CFT) policies. Its objective was to identify the state of the art on the subject and some of the main opportunities, challenges and risks which should be considered in the ongoing process of a digital euro. The research was based on a critical review of reports and surveys about CBDCs produced by central bank community, international institutions and European Union agencies, the regulatory framework and international standards about data protection and AML/CFT, complemented by academic and professional experts’ literature. It was conducted under a qualitative method following the premise that in Fintech innovation is crucial to understand current and emerging regulations that can be relevant. Digital euro’s architecture, independently of the adopted model (accountbased, token-based or hybrid), should: (1) allow CBDC holders identification and comprise traceability mechanisms in accordance with AML/CFT requirements; (2) respect the General Data Protection Regulation, namely data protection by design and by default through privacyenhancing technologies. The status of the European Central Bank and national central banks of euro countries is incompatible with their subjection to the legislation on AML/CFT applicable to the participants on digital money transfers market, so all the operations related with the end-users must be full intermediated by private sector entities submitted, beyond financial supervision, to guidelines, regulation and supervision by AML/CFT authorities.